Contribution of Senior Citizens to Employment Generation - Devkota, Balaram (Educational Journal, 2023)
The labor market of Nepal is shrinking with the migration of youth to foreign countries in search of employment opportunities. Rapid population ageing further exacerbates the situation, eventually affecting the national economy and development processes. Unlike many nations around the world, Nepal is yet to adopt policies realizing the impacts of population ageing. With less experience and fewer skills, young people often encounter difficulties accessing work. On the other hand, senior citizens have lifetime experience and expertise, which, if transferred to the younger population, can bring changes to the employment scenario among the younger generation and increase their employment rate. It was focused on exploring the skills and expertise of senior citizens in terms of procreating income-generating. The study was conducted in Sindupalchowk, Kavrepalanchowk, and Kathmandu districts with a sample size of 318 senior citizens. Locations were purposively selected keeping in mind the geographical structure of the areas and availability of respondents. Adopting the Snowball Sampling technique, senior citizens active in income-generating activities like agriculture/farming, entrepreneurship, factories, cooperatives, education sector, and others were identified for primary data collection. The snowball sampling was used because it had supported the same cohort of an ageing population and located the old age people in the locality. Besides, qualitative data were gathered through desk review, FGDs, and formal/informal meetings. The majority of the senior citizens interviewed were active in their professions and were contributing to their family economies. They had developed expertise after dedicating a significant portion of their life working in a particular field. Having made progress with their works, the senior citizens see great prospects of their current professions even in the next ten years and highly recommend young generation to involve in similar occupations. Young generations have great prospects ahead of them but require proper guidance.